PRARANCANGAN PABRIK AMIL ALKOHOL DARI AMIL KHLORIDA DAN NATRIUM HIDROKSIDA KAPASITAS 30.000 TON/TAHUN - , EWINSO RAJAGUKGUK; , Ir. Agus Prasetya, M.Eng., Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The plant of which 30.000 ton/year of amyl alcohol as the prominent product and 15.525 ton/year of amilen as the side product is made by reacting the basic material of amyl chloride for 63.371,8 ton/year and 48% of NaOH for 51.186,2 ton/year aided by sodium oleic as the catalyst for 1800,8 ton/year. A utility unit as the supporting unit in the production process of this plant includes water, steam, electricity, and pneumatic. The utility needs NaCl for 15.523,2 kg/year, NaOH for 9.187,2 kg/year, Na2CO3 for 250.905,6 kg/year, coagulant for 17067,6 kg/year, Na2HPO4.2H2O for 22.096,8 kg/year, fuel (diesel type) for 118.742,4 liter/year, boiler fuel (fuel oil type) for 9.904.277 liter/year, and electricity for 505,2 kW. This plant has 200 employees. The land of this plant is 30.000 m 2 . This plant is located in Cilegon. The fixed capital of this plant is $ 23.611.397,49 or Rp 224.308.276.150 and the working-capital is $ 28.050.017,63 or Rp 266.475.167.555. From the result of economic analysis, it can be obtained that the break event point (BEP) is 46,5 %. Whereas, the pay out time (POT) before tax is 2,068 years, while after tax is 3,029 years. Furthermore, the return on investment (ROI) before tax is 38,37 % and after tax is 23,02%. In addition, the discounted cash flow is 20,549 %. Therefore, this plant is interesting to be analyzed further.